Psychophysiological and psychological features of elite young volleyball players - E. I. Dulova; A. A. Reshetova; A. E. Igolkina; D. A. Kravchuk; I. N. Mitin; K. S. Nazarov; A. V. Zholinskiy (National Electronic Information Consortium (NEICON), 2020)
Objective: to analyze the psychological and psychophysiological features of effective volleyball play. Materials and methods: the study involved 19 female athlets with average age of 17±1 years. The study was conducted during the pre-competition period. Personality traits, sport motivation, coping strategies, emotional burnout, skills of mental training and visualization, were assessed by adapted Russian-language versions of questionnaires «Freiburg multi-factor personal questionnaire (FPI)», «Sport motivation scale (SMS)», «The Sport Imagery Questionnaire (SIQ)», «Strategic Approach to Coping Scale (SACS)», «Maslach burnout inventory». The levels of chronic and acute stress were assessed by «Acute and chronic stress scale». Attentional set-shifting, concentration of attention were examined by the Munsterberg test and the «Entangled lines» test. The speed and stability of sensorimotor functioning were assessed by Simple Reaction Time test and Choice Reaction Time test. Stress load was simulated by the game-biofeedback approach to examine the effectiveness of self-regulation. The obtained data were compared with the assessment of athletes' gaming efficiency. Results: Revealed significant connection between game effectiveness and the reduced level of stress: high speed, reaction stability, internal motivation, decreased neuroticity, depressiveness, aggressiveness, emotional lability, developed skills of self-regulation, visualization and ideomotor training are discussed. Conclusions: Revealed psychological and psychophysiological features might be considered as components of the young female volleyball players' model psychophysiological state.